2007
DOI: 10.1007/s00441-007-0531-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of beclin 1, a bcl-2-binding, autophagy-related protein, in the human ovary: possible relation to life span of corpus luteum

Abstract: Ovarian tissue homeostasis is maintained by highly regulated cyclic phases of cell proliferation/differentiation and programmed cell death. Compelling evidence indicates that both apoptotic and autophagic types of programmed cell death are involved in the regression of the corpus luteum (CL) in primate species. Beclin 1 is an autophagy-related protein that is involved in the inter-relationships between apoptosis and autophagy, through interaction with the anti-apoptotic protein bcl-2. We studied the presence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 41 publications
1
35
1
Order By: Relevance
“…In vitro analyses of murine prepubertal oocytes showed that both apoptotic and autophagic processes were involved in the cell death of the oocytes (Lobascio et al 2007, Escobar et al 2008a, 2008b. The importance of autophagy in follicular atresia has been demonstrated across multiple species including Drosophila, teleostei, caecilians, stingray, dove, quail, sheep, rats, and humans (Rosales--Torres et al 2000, Velentzas et al 2007, Gaytan et al 2008, Santos et al 2008, Zarnescu 2004.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro analyses of murine prepubertal oocytes showed that both apoptotic and autophagic processes were involved in the cell death of the oocytes (Lobascio et al 2007, Escobar et al 2008a, 2008b. The importance of autophagy in follicular atresia has been demonstrated across multiple species including Drosophila, teleostei, caecilians, stingray, dove, quail, sheep, rats, and humans (Rosales--Torres et al 2000, Velentzas et al 2007, Gaytan et al 2008, Santos et al 2008, Zarnescu 2004.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, autophagy is suggested to promote cell survival rather than cell death in the corpus luteum life span. 34,35 It is conceivable that survival autophagy occurs in addition to apoptosis in regressing ovary follicles. This suggestion is supported by findings of autophagosomes in freshly harvested human granulosa cells.…”
Section: Discussionmentioning
confidence: 99%
“…At the molecular level, there is a specific endocrine voltage-activated sodium channel in the human ovary from which downstream signalling induces autophagy in CL regression (Bulling et al 2000). Conversely, there is increased beclin-1 expression in CL cells during pregnancy as well as in pathological conditions when the CL survives longer than normal, implicating autophagy in granulosa cell survival as well (Gaytán et al 2008). True to the double-edged reputation of autophagy, these findings suggest opposing roles for autophagy in CL dynamics.…”
Section: Ovaries and Testesmentioning
confidence: 94%